2019
DOI: 10.1155/2019/7515346
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Candidate: Heparin-Binding Protein Steps onto the Stage of Sepsis Prediction

Abstract: Sepsis is a systemic inflammatory response syndrome caused by infection. With high morbidity and mortality of this disease, there is a need to find early effective diagnosis and assessment methods to improve the prognosis of patients. Heparin-binding protein (HBP) is a granular protein derived from polynuclear neutrophils. The biosynthetic HBP in neutrophils is rapidly released under the stimulation of bacteria, resulting in increased vascular permeability and edema. It is reasonable to speculate that the HBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 91 publications
0
38
0
Order By: Relevance
“…Previous studies have shown the molecular pathomechanisms of HBP involved in vascular leakage, chemotaxis and inflammation in the course of sepsis, cardiac and respiratory failure and various infections. It has been identified not only as a promising diagnostic marker, but also has prognostic relevance for severity of disease (Yang et al, 2019). However, the purpose of this study was not to determine the role of GrA and HBP in the pathogenesis of AKI during sepsis, but to investigate their significance in AKI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the molecular pathomechanisms of HBP involved in vascular leakage, chemotaxis and inflammation in the course of sepsis, cardiac and respiratory failure and various infections. It has been identified not only as a promising diagnostic marker, but also has prognostic relevance for severity of disease (Yang et al, 2019). However, the purpose of this study was not to determine the role of GrA and HBP in the pathogenesis of AKI during sepsis, but to investigate their significance in AKI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…HBP, refers to granule proteins derived from neutrophils, has antimicrobial activity and active roles in inflammatory responses 19 . HBP is positively correlated with PCT levels and may therefore also serve as an indirect biomarker for early diagnosis of infection 20 . It has been studied in several acute diseases, such as acute kidney injury, 21 acute lung injury, 22 bacterial skin infection, 23 acute bacterial meningitis, 24 but rarely in AP.…”
Section: Discussionmentioning
confidence: 99%
“… 19 HBP is positively correlated with PCT levels and may therefore also serve as an indirect biomarker for early diagnosis of infection. 20 It has been studied in several acute diseases, such as acute kidney injury, 21 acute lung injury, 22 bacterial skin infection, 23 acute bacterial meningitis, 24 but rarely in AP. IL‐6 is one of the more well‐studied cytokines that rapidly decreases within 48 h unless severe infection persists.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells are the primary targets of HBP released in the circulation and this protein plays a major role in the mechanism of capillary leakage, while it amplifies inflammatory effects by inducing cytoskeletal rearrangement and resulting in increased permeability of the vascular endothelial barrier [17,19]. Antigens, inflammatory factors, cytokines and enzymes can stimulate PMN to release HBP by exocytosis [20,21]. Studies in sepsis have indicated that the sensitivity and specificity of HBP are varied, compared to C-reactive protein (CRP) or procalcitonin (PCT), as an independent predictor of clinical outcome in severe infection [22,23].…”
Section: Introductionmentioning
confidence: 99%